Peranan Audit Internal dalam Menunjang Efektivitas Pengendalian Internal Penjualan - Jamaludin, Abdusai (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
This study aims to determine the role of internal audit in supporting the effectiveness of internal control sales at CV. Mitra Mulia Sejahtera in 2014 the variables used in this study are internal audit and internal sales control. The measurement scale used is the ordinal scale. The population in this study were all employees of CV. Mitra Mulia Sejahtera, while the sample used was 30 employees at CV. Mitra Mulia Sejahtera. The types of data used are primary data and secondary data. The data that was successfully collected was then analyzed using validity and reliability tests, classical assumption test, namely normality, simple regression analysis, hypothesis testing using t test, and coefficient of determination test. The results of the validity test showed that all questions for the independent variable and the dependent variable were declared valid. The results of the reliability test showed that the independent variable instrument and the dependent variable were reliable. The results of the classical assumption test, namely the normality test, show that the role of internal audit in supporting the effectiveness of internal control is normally distributed. The results of hypothesis testing (t-test) show that internal audit has a significant effect on the effectiveness of internal sales controls. And the results of the coefficient of determination test show that the internal audit variable is able to explain the effectiveness of internal